Nucleate pool boiling enhancement by ultrafast water permeation in graphene-nanostructure. (February 2019) - Lay, Kok Keong; Ong, Jun Siong; Yong, Kai Yen; Tan, Ming Kwang; Hung, Yew Mun
Abstract: Nucleate boiling efficiency can be significantly enhanced using the nanostructured graphene surface. The wettability of the graphene nanoplatelets (GNPs) coated surface is tunable using thermal curing process. The uncured GNPs surface is hydrophobic in nature while the cured GNPs surface manifests a hydrophilic characteristic and the latter performs better than the former in the nucleate boiling regime. Ultimately the ultrafast water permeation property of the cured GNPs enhances the efficiency of nucleate pool boiling, leading to a maximum enhancement of 151% in the boiling heat transfer coefficient and 154% in the vapor mass flow rate. The boiling performance of the uncured GNPs surface is also enhanced despite its hydrophobicity. Hence, the enhancement in boiling is not solely attributed to the surface wettability. The enhancement is attributed to the fascinating ultrafast water permeation property of graphene on top of its nanoporous structure. The unimpeded fast water transport within the nanochannel-network of GNPs facilitates the fast absorption of latent heat of vaporization by the water molecules, leading to a substantial increase in the nucleation, growth and departure of vapor bubbles. We propose a new explanation on the role of graphene coating on nucleate pool boiling enhancement. This study provides important insights into the effects of ultrafast water permeation property of graphene on the nucleate boiling heat transfer.